CODE-SWITCHING BETWEEN NURSE-PATIENT COMMUNICATION: BILINGUAL INTERACTION SOCIETY - Indah Nur’Aini; Qori Fanani (British : Jurnal Bahasa dan Sastra Inggris, 2019)
The objective of this research is to investigate the code-switching in communication between nurse and patient which takes place in South Malang. The people speak Indonesian language, Javanese, and Madurese; therefore, they are living in a bilingual society. This research uses questioner to collect demographic data and audio recordings to collect the communication production between nurse and patient while a nurse is giving an initial assessment. The data are analyzed by looking at the code-switching from a sociolinguistic view. The result shows that nurse and patient use code-switching not because they cannot speak one of the languages but they do not want to throw respect to each other. It can be seen from the word used in Javanese which is part of the mid-high Javanese speech level.